Homogeneous distribution of fatty ester‐based active cosmetic ingredients in hydrophilic thin films by means of nanodispersion. (4th September 2020) - Munnier, Emilie; Al Assaad, Almar; David, Stephanie; Mahut, Frédéric; Vayer, Marylène; Van Gheluwe, Louise; Yvergnaux, Florent; Sinturel, Christophe; Soucé, Martin; Chourpa, Igor; Bonnier, Franck
Abstract: Objective: Cosmetic films and patches are interesting forms to promote skin penetration of active ingredients as they ensure their long stay on the treated zone of the skin. Nevertheless, currently developed films and patches are most of all hydrophilic and are not adapted to the hydrophobic molecules. The aim of this study was to establish whether nanodispersion of fatty acid‐based active cosmetic ingredients (ACI) could be a manner to introduce high concentrations of those ACI in hydrophilic films. Methods: Punica granatum seed oil hydroxyphenethyl esters (PHE) constitute a commercialized lipolytic cosmetic ingredient obtained by enzymatic conjugation of tyrosol to long‐chain fatty acids and to enhance its skin diffusion. Nanodispersions of PHE were prepared by a green emulsion‐solvent evaporation process and dispersed in polyvinyl alcohol films. Raman imaging coupled to multivariate analysis was used to study the distribution of PHE in the films. Results: Nanodispersions of PHE combined with antioxidant vitamin E and stabilized by Pluronic® F127 were successfully prepared. The nanodispersions show a spherical shape and a hydrodynamic diameter close to 100 nm. Raman images analysis with multivariate approaches showed a very homogeneous distribution of PHE nanodispersions in the films compared to free PHE introduced as an ethanol solution. Conclusion: Nanodispersions of hydrophobic fatty acid‐based ingredients seem to be relevant method to introduce this type of ingredient in hydrophilic film matrix. The co‐suspension with vitamin E limits their degradation in time. Abstract : The nanodispersion of a fatty‐ester based active cosmetic ingredient permitted its homogeneous dispersion in hydrophilic PVA thin film. The homogeneity was assessed by Raman imaging coupled to chemometrics. Resumé: Objectif: Les films et patchs cosmétiques sont des formes intéressantes pour augmenter la pénétration cutanée des actifs cosmétiques car ils assurent une exposition prolongée de la zone de peau traitée ce qui favorise la diffusion. Néanmoins, les films et patchs actuellement développés sont majoritairement de nature hydrophile et ne sont pas adaptés aux molécules hydrophobes. Le but de cette étude est d'établir si la nanodispersion d'actifs cosmétiques à base d'acides gras peut être un moyen d'introduire des concentrations élevées de ces actifs dans des films hydrophiles. Méthodes: Les esters hydroxyphénéthyliques de l'huile de graines de grenade Punica granatum (PHE) sont commercialisés comme un agent lipolytique. Cet actif obtenu par conjugaison enzymatique du tyrosol à des acides gras à longue chaîne ce qui favorise sa pénétration cutanée. Des nanodispersions de PHE ont été préparées par un procédé d'émulsion‐ évaporation développé avec un solvant vert. Ces nanosystèmes sont ensuite dispersées dans des films d'alcool polyvinylique. L'imagerie Raman couplée à une méthode d'analyse statistique multivariée a été utilisée pour étudier la distribution des PHE dans les films. Résultats: Des nanodispersions de PHE associées à de la vitamine E antioxydante et stabilisées par Pluronic® F127 ont été préparées avec succès. Les nanodispersions présentent une forme sphérique et un diamètre hydrodynamique proche de 100 nm. L'analyse d'images Raman au moyen d'une approche multivariée a montré une distribution très homogène des nanodispersions dans les films par rapport aux PHE libres introduits sous forme de solution éthanolique. Conclusion: Les nanodispersions d'ingrédients hydrophobes à base d'acides gras semblent être une méthode pertinente pour introduire ce type d'ingrédient dans la matrice de film hydrophile. L'introduction de vitamine E dans les nanodispersion ralentit leur dégradation.